Establishing discriminative control of responding using functional and alternative reinforcers during functional communication training. - Fisher, W W (1998)
Functional communication training (FCT) is a popular treatment for problem behaviors, but its effectiveness may be compromised when the client emits the target communication response and reinforcement is either delayed or denied. In the current investigation, we trained 2 individuals to emit different communication responses to request (a) the reinforcer for destructive behavior in a given situation (e.g., contingent attention in the attention condition of a functional analysis) and (b) an alternative reinforcer (e.g., toys in the attention condition of a functional analysis). Next, we taught the participants to request each reinforcer in the presence of a different discriminative stimulus (SD). Then, we evaluated the effects of differential reinforcement of communication (DRC) using the functional and alternative reinforcers and correlated SDs, with and without extinction of destructive behavior. During all applications, DRC (in combination with SDs that signaled available reinforcers) rapidly reduced destructive behavior to low levels regardless of whether the functional reinforcer or an alternative reinforcer was available or whether reinforcement for destructive behavior was discontinued (i.e., extinction).